The Response of Seed Germination and Seedling Growth of Woody Borreria (Hedyotis verticillata Lam.) Towards Aqueous Curry (Murraya koenigii) Leaves Extract - Noor Iffa Hanis Zakaria (2019)
The chemical herbicide is favorably used in a massive field of the agriculture industry in Malaysia but in contrast, it gives few negatives side impact to environment and ecosystem. It has diverse immense consequences on the human being, soil, groundwater, disturbing conservation of ecosystem especially impact to nature. Allelopathy approach of potential crop is a suitable alternative that should be explored to have sustainable weed management. The present study is to determine the phytotoxic effect of aqueous curry (Murraya koenigii) leaves extract on the emergence and seedling growth of the bioassay species, woody borreria (Hedyotis verticillata) under laboratory and nursery condition. The seed and seedling of bioassay species were treated with different concentration of aqueous curry leaves extract at 0, 20, 40, 60, 80 and 100g/L (laboratory) and 0, 50, 100, 150, 200 and 250g/L (nursery). The results showed that the aqueous curry leaves extract possesses a significant inhibition on seed emergence, shoot fresh weight and radicle length of H. verticillata at 100g/L concentration, where it reduced by almost 100% when applied as pre-emergence under laboratory condition. Meanwhile, the optimal concentration for shoot fresh weight, shoot height and root length is at 250g/L of aqueous curry leaves extract with 21% inhibition level under nursery condition. Conversely, there is an only slight reduction in shoot fresh weight, shoot height and root length of H. verticillata when treated at soil surface as post-emergence under nursery condition. The results obtained might vary between laboratory and nursery as soil media tend to have a flexible chemical reaction in response to aqueous curry leaves extract. The inhibition level increase with incremental of extract concentration as the probable reason for inhibitory activity of aqueous curry leaves extract may be due to the presence of allelochemicals. These results suggest that curry leaves can be a good source to produce natural herbicide for weed management while it is also an eco-friendly compound for the environment and human being.